Implementation of a SenseMaker® research project among Syrian refugees in Lebanon. Issue 1 (1st January 2017) - Bakhache, Nour; Michael, Saja; Roupetz, Sophie; Garbern, Stephanie; Bergquist, Harveen; Davison, Colleen; Bartels, Susan
ABSTRACT: The Syrian conflict has displaced over 1.2 million Syrians into Lebanon. As a result of displacement, some Syrian families are turning to child marriage as a coping mechanism. The prevalence of early marriage has reportedly increased and the average age of marriage decreased during the crisis. The aim of the project was to understand the underlying factors contributing to child marriage among Syrian refugees in Lebanon using Cognitive Edge's SenseMaker®. This manuscript explores the process of implementing this novel research tool in a humanitarian setting. Twelve interviewers conducted SenseMaker® interviews with married and unmarried Syrian girls, Syrian parents, as well as married and unmarried men. Participants were asked to share a story about the lives of Syrian girls in Lebanon and to self-interpret the narratives by answering follow-up questions in relation to the story provided. Data collection occurred across three locations: Beirut, Beqaa, and Tripoli. In total 1422 narratives from 1346 unique participants were collected over 7 weeks. Data collection using SenseMaker® was efficient, capable of electronically capturing a large volume of quantitative and qualitative data. SenseMaker® limitations from a research perspective include lack of skip logic and inability to adjust font size on the iOS app. SenseMaker® was an efficient mixed methods data collection tool that was well received by participants in a refugee setting in Lebanon. The utility of SenseMaker® for research could be improved by adding skip logic and by being able to adjust font size on the iOS app.